Developing accessible routes in historic environments for wheelchair users using a smart mobile application - Hüseyin Özdemir (Ain Shams Engineering Journal)
In cities with historical heritage, wheelchair users cannot benefit from urban spaces due to the lack of design in the physical environment. In this study, Konya city centre (Turkey), which has a historical richness for the solution of this problem, is analysed according to Turkish Standard (TS9111), The Americans with Disabilities Act (ADA) and the United Nations (UN) standards for wheelchair users. Based on the data obtained, problems where accessibility cannot be provided are identified. These problems were solved by developing an “accessible route” mobile application through “Flutter software developed by Google”. With the ease provided by the developed mobile application, wheelchair users can be easily integrated into the historical environment. The mobile application developed within the scope of this study can also be created by incorporating a series of alternatives, such as different language options, various locations and eating and drinking places and can be expanded in other research.